Integritas Mahasiswa : Lawan Kecurangan (Fraud) Sejak Bangku Kuliah di Universitas Pertiwi Bekasi - Satria Berbudi; Cici Rosmala; Aulia Rahmi; Ari Sarah Sofura; Siti Nuridah; Fauzobihi Fauzobihi; Zainuri Zainuri; Akhmad Suhada (Kolaborasi : Jurnal Hasil Kegiatan Kolaborasi Pengabdian Masyarakat, 2025)
The phenomenonoccurring in various universities shows an increase in cases of academic fraud, such as cheating, plagiarism, research data manipulation, and misuse of technology in the learning process. This behavior not only undermines academic integrity, but also has the potential tocreate a mindset of cheating that carries over into the workplace. Integrityis a fundamental value that forms the moral foundation of every aspect oflife, both in education and in the workplace. In the context of higher education, students are expected not only to excel academically,but also to possess honesty, responsibility, and strong professional ethics.Accountants are future professionals who will be directly involved inthe management and financial reporting of organizations. This profession demandsa very high level of honesty and integrity, because the accuracy andreliability of financial reports form the basis for business and public decision-making. However, in practice, there are many cases of accounting fraud, such as budget mark-ups, financial statement manipulation, creative accounting, and data misstatement, which occur due to weak values of integrity and moral responsibilityamong individuals. If dishonest behavior has already been established during college—for example, in the form of cheating, manipulating assignment data, or falsifying lab reports—then the risk of bringing similar habits into the workplace will be even higher. Integrity is a core competency (core comp) that determines a person's quality as an organizational asset